Impact of a Short-Term Water Abstinence on Airway Hyperresponsiveness in Elite Swimmers. Issue 4 (July 2017) - Bohm, Philipp; Hecksteden, Anne; Meyer, Tim
Abstract : Objective: To investigate the effect of a swimming break on airway hyperresponsiveness (AHR) and to evaluate perception of bronchoconstriction-related symptoms after methacholine challenge testing (MCT). Design: Observational, controlled study. Setting: University department. Participants: Overall, 25 healthy, elite, competitive swimmers aged ≥14 years from the local Olympic training center and 25 healthy control subjects. Independent Variable: Duration of water abstinence. Main Outcome Measures: Primary outcome measures were a positive MCT with a provocation dose (PD) and the perception score of bronchoconstriction-related symptoms at visit 1 (V1, training period) and visit 2 (V2, after swimming break). Results: In the study, 13 swimmers (52%) and 10 control subjects (40%) showed AHR. The PD did not differ significantly between V1 and V2 in the swimmers ( P = 0.81) or in the control subjects ( P = 0.74). No correlation of fraction of exhaled nitric oxide with the PD could be established in both the groups (swimmers: P = 0.97; controls: P = 0.99). The majority of swimmers with AHR were asymptomatic, and only minimal differences in perception of bronchoconstriction-related symptoms between swimmers and control subjects were observed ( P = 0.23). Conclusions: A swimming break of 25 ± 8 days does not seem sufficient to significantly reduce AHR in elite swimmers. Thus, relevant and systematic effects of short-term water abstinence on AHR seem unlikely. Because the majority of swimmers remain asymptomatic, AHR may escape routine screening examinations. The impact of AHR on athletic performance and the long-term clinical consequences remain to be clarified.